Assessing operational status of BRAC Gonokendra Pathagar - Khan, Md. Kaisar Ali (BRAC Research and Evaluation Division (RED), 2020)
This study aimed at assessing operational status of the BRAC Gonokendra pathagars. Sixty randomly selected pathagars were surveyed. Data was collected on the basis of some performance indicators. It was found that the number of male members and their daily attendance in the General and Small type pathagars was higher compared to females. The number of female members and their daily attendance in the female type pathagars was predominantly higher than males. On average, about 60 users daily attended the pathagars, and 183 books were found to be borrowed per month in the General type pathagars, followed by 120 and 74 in the female and small type pathagars respectively. The pathagars had an average of 969 books. On average, the community put forward about Tk.50,000as a reserve fund for the General type pathagars, which was Tk.56,000 and Tk.25,000 for Female and Small type pathagars respectively. Sixty-seven percent of the pathagars were established in pacca buildings, followed by 25% in Tin-shed buildings. The interior space of most of the pathagars, and its environmental conditions were found to be satisfactory. The majority of the pathagars organized cultural activities on a regular basis but, very few of them organized social activities. The major findings of this study indicate that community participation, especially at the initial stage of the pathagar's establishment was satisfactory, but participation of both sexes together in development activities particularly in rural areas seemed to be limited. There still some room for improvement and further measures to achieve higher level performance.